2003
DOI: 10.1099/vir.0.18703-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of intercellular adhesion molecule-1 by the human cytomegalovirus transactivators IE2p86 and pp71 is mediated via an Sp1-binding site

Abstract: Human cytomegalovirus (HCMV) infection of transplant recipients is frequently associated with allograft vasculopathy and rejection. One potential mechanism is vascular injury from HCMVtriggered, immunologically mediated processes. HCMV infection has been shown to increase the expression of intercellular adhesion molecule-1 (ICAM-1). The objective of this study was to determine the molecular basis of HCMV-enhanced ICAM-1 gene expression. Transient transfection experiments identified the IE2p86 protein as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 81 publications
2
22
0
Order By: Relevance
“…These results further suggest that both NF-B and NFAT signaling contribute to thrombininduced ICAM-1 expression in endothelial cells. Our findings add to a growing body of evidence suggesting that inducible transcription factors interact with the intronic enhancer DNA elements and play critical roles in gene transcription (15,18,31). Another study showed that MHC class I-related neonatal Fc receptor for IgG induced by TNF-␣ is associated with NF-B binding to the intronic sequence (18).…”
Section: Knockdown Of Either P65/rela or Nfatc1 In Endothelial Cells mentioning
confidence: 81%
See 1 more Smart Citation
“…These results further suggest that both NF-B and NFAT signaling contribute to thrombininduced ICAM-1 expression in endothelial cells. Our findings add to a growing body of evidence suggesting that inducible transcription factors interact with the intronic enhancer DNA elements and play critical roles in gene transcription (15,18,31). Another study showed that MHC class I-related neonatal Fc receptor for IgG induced by TNF-␣ is associated with NF-B binding to the intronic sequence (18).…”
Section: Knockdown Of Either P65/rela or Nfatc1 In Endothelial Cells mentioning
confidence: 81%
“…A number of recent studies have shown that inducible transcription factors binding to intronic enhancer elements play critical role in gene transcription (15,18,31). There is, however, no evidence to indicate whether the inducible transcrip-tion factors interact with an intronic region of the ICAM-1 gene and contribute to the transcription of ICAM-1 gene.…”
mentioning
confidence: 95%
“…Dependence on ATF recognition sites was also observed in cotransfection studies that investigated the response of the HCMV US11 promoter in the presence of pp71, although in this case the IE protein IE86 was also present (7). The promoter for intercellular adhesion molecule 1 was activated by pp71, in conjunction with IE86, via Sp1 recognition sites (32). Limited stimulation of endogenous intercellular adhesion molecule 1 expression by pp71 alone was also reported in these studies.…”
mentioning
confidence: 74%
“…Similar to many herpesvirus gene products that have been investigated, pp71 exerts multiple roles during the cytomegalovirus life cycle. It is a transactivator of both viral and cellular genes and can synergize with the transactivating activities of IE2p86 and ppUL35 (6,17,27,29,42). pp71 also increases the infectivity of viral DNA in a manner independent from its function as a transactivator of the IE1 and IE2 genes (3).…”
Section: Discussionmentioning
confidence: 99%